FORMULASI MASKER GEL PEEL-OFF PERASAN LIDAH BUAYA (Aloe vera L.) DENGAN GELLING AGENT POLIVINIL ALKOHOL - Santoso, Ivan; Prayoga, Tria; Agustina, Ika; Rahayu, Wiwit Setya (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2020)
Aloe vera (Aloe Vera L.) is a plant which commonly used by local people as moisturizer. The usage of aloe vera can be applied in form of peeled off gel mask with polyvinyl alcohol as gelling agent. The goal of this research is to determine the influence of increase of polyvinyl alcohol as gelling agent to the formulation of peeled off mask from aloe vera juice. The formulation was made in a few concentration, 10%, 12%, and 14% by adding 0,5% of aloe vera juice. After that, the formulation evaluated for 4 weeks about the organoleptics, homogenity, pH, drying time and viscosity. The date of pH test and drying time analyzed by using one way ANOVA statistically and then followed by Tukey HSD test and the viscosity analyzed by using Kruskall Wallis statistically which result in the significantcy less than 0,05 that mean there are difference in drying time and viscosity, on the other hand there is no difference in pH.